KOMUNIKASI KELUARGA: BAGAIMANA ORANG TUA BERINTERAKSI DENGAN ANAK GEN Z - Harahap, Machyudin Agung; Yusnita, Titien; Adeni, Susri (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Harmonious communication and interaction are needed in the family. However, communication is not always good. There are many obstacles faced by parents, especially those who have Generation Z (Gen Z) children. For this reason, there is a need for education for parents in Ciomas Rahayu Village, Ciomas District. Bogor Regency. This is because there are many complaints from parents when communicating with Gen Z children. Parents feel that their children prefer gadgets rather than activities with the environment and family. Education by providing materials, discussions and questions and answers as well as simulations made parents understand how to communicate with Gen Z children. Participants were also shown videos about healthy internet and education with games so they understood the material presented. From the material presented, discussions and simulations carried out, parents who have Gen Z children understood how to behave and communicate with their children. Parents do not always give advice or improve conversation orientation factors, but a warm conformity orientation approach in a relaxed atmosphere and not dominating one member over another is effective in changing children's negative attitudes.